An object-oriented architecture for transmission simulation of image and video with multiple description coding over high-speed optical fibre channels - Braz, Rui Pedro Quaresma (2010)
This dissertation addresses the problem of providing a tool with an object-oriented architecture in order to allow the possibility of simulate the transmission of images and/or videos coded with Multiple Description over high-speed optical fibre channels. In order to solve the problem proposed the choice was a simulator, once the advantage of this solution when compared to a real experiment as several advantages. The solution presented on this dissertation presents several advantages when compared with the solutions already analysed that only allows to analyse some physical phenomena that occur on optical fibre, not filling the requirements pretended to simulate. The proposed solution was developed using an object-oriented architecture, providing the possibility of increment the number of scenarios possible to simulate. On this dissertation all of the development process is described, since the structure of the proposed solution, to the classes developed as long as the Graphical User Interface implemented. The simulation results presented were obtained using a Multiple Description Coding algorithm.